Teaching Business Ethics Through Meditation - La Forge, Paul G. (Journal of business ethics, 1997)
The purpose of this article is to show how meditation can be used to help a student to become an ethical person. Discursive and non-discursive meditation give the student an awareness of ethical issues and lead to the discovery and application of models of ethical conduct. In part one, the student is led through non-discursive meditation to discover him/her self as an ethical person. The student is also given the tools to explore ethical issues. Part two discusses a transition stage from non-discursive to discursive meditation. The student is led to use non-discursive meditation to construct an ethical value system and apply it to his/her own life. An art medium is especially helpful at this stage. Discursive meditation gives the chance for the student to compare who he/she is with what he/she should be. Part three discusses four elements in the construction of an ethical vision with discursive meditaton: First, a picture of reality; second, models of ethical rules; third, models of ethical conduct; fourth, current personal and social values. The conclusion contains a description of the ethical person.